Mapping the operation of Airbnb in Sri Lankan cities - Munasinghe, Lasika Madhawa; Gunawardhana, Terans; Wickramaarachchi, N.C.; Ariyawansa, R.G. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Airbnb is most famous as a part of the growing “sharing”, “peer-to-peer”, or “digital” economy where the platform transformed the traditional tourist accommodation services through its novel business model. In order to comprehend the influence of Airbnb on the tourism and hospitality landscape, it is critical first to understand the market and how Airbnb operates. Therefore, in this study, we explore the operation of Airbnb in Sri Lanka using descriptive statistics and maps by analysing the scrapped data of the Airbnb website. The study results show that Airbnb has been well established on Sri Lankan soil as an alternative accommodation service provider, and the listings have been scattered across the country. However, most listings tend to concentrate in the city centres of famous touristic districts and tourist resort regions in Sri Lanka. These findings will provide a valuable avenue for further investigation of the operation of Airbnb in Sri Lanka.